The developmental approach to child and adult health - Gabriella Conti; James J. Heckman (Institute for the Study of Labor (IZA), 2012)
Pediatricians should consider the costs and benefits of preventing rather than treating childhood diseases. We present an integrated developmental approach to child and adult health that considers the costs and benefits of interventions over the life cycle. We suggest policies to promote child health which are currently outside the boundaries of conventional pediatrics. We discuss current challenges to the field and suggest avenues for future research.
Keywords: I12; I18; 330; health; prevention; remediation; capabilities; technology of capability formation; Gesundheitsvorsorge; Kinder; Lebenszyklus; Erwachsene; Gesundheit; Kosten-Nutzen-Analyse